PENGEMBANGAN MEDIA CERITA BERGAMBAR BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN MINAT BACA DAN KARAKTER JUJUR (Penelitian D&D untuk Siswa Kelas III SDN Tanah Baru Kota Cirebon) - Nilamsari Ramadhanti, - (2022)
ABSTRACT PICTURE STORY MEDIA DEVELOPMENT BASED ON LOCAL WISDOM TO IMPROVE READING INTEREST AND HONEST CHARACTER (D&D Research for Third Grade Students of SDN Tanah Baru, Cirebon City) By Nilamsari Ramadhanti 1807838 The purpose of this study was to determine whether the development of picture story designs based on local wisdom could increase reading interest and honest character in third grade elementary school students and to find out the validation results of developing illustrated story media to increase reading interest and honest character. This research was conducted to overcome the problems that occurred to third grade students at Tanah Baru Elementary School, Cirebon City, the problems were found based on the results of interviews with third grade guardians at Tanah Baru Elementary School Cirebon City. This study also uses illustrated story media to increase the attractiveness of students to reading as well as local wisdom of Cirebon City, it is also hoped that the stories raised can instill honest characters in students. The data collection instrument used in this study was in the form of an assessment format, while the technique for collecting data used the interview method and also expert judgment. This study uses a qualitative approach, D&D method and ADDIE development design. Based on the results of the design / media expert data processing, the validity criteria for the design or media were obtained by 100%. Meanwhile, based on the results of material expert data processing, the validity criteria for the material were obtained at 97.5%. Then the level of validity of both can be said to be very valid, can be used without revision. Validity is only done once because the results obtained from the two experts are very valid. Keywords: Picture story media, increasing reading interest, local wisdom.